Sustainable Bonds in Indonesia: A Systematic Literature Review and Future Prospects - Putri, Fatwasari Soeratno; Aryani, Y. Anni; Setiawan, Doddy (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
The aim of this study is to review publications on sustainable bonds in Indonesia between 2017 and 2024 using a systematic literature review (SLR). Using the SPAR-4-SLR methodology, 30 relevant articles were sourced from Scopus and Sinta 1 and 2 databases, identified through keywords including "sustainable bond, "green bond", "green sukuk, "social bond", "sustainability bond", "sustainability-linked bond", "eco-bond", "blue bond", "green Islamic bond", "SRI sukuk", "ESG bond", "climate bond", "SDG bond", and "Indonesia. A bibliometric analysis using Vosviewer was performed to map keyword co-occurrences, revealing green bonds and green sukuk as dominant themes. The study identifies key drivers of sustainable bonds such as investor awareness, regulatory advancements, green marketing, and challenges like high capital costs, greenwashing risks, and regulatory inconsistencies. Emerging instruments such as blue sukuk, sovereign climate-aligned bonds, and earthquake bonds offer new avenues for sustainable finance in Indonesia. This research underscores the critical role of sustainable bonds in achieving climate goals and social inclusion while emphasizing the need for broader studies on underrepresented bond types.